Cascaded Metasurface Interferometer for Multipath Interference with Classical and Quantum Light - Aschwanden, Rebecca; Claro-Rodríguez, Nicolás; Zhao, Ruizhe; Kallert, Patricia Anna Maria; Krieger, Tobias; Buchinger, Quirin; Covre da Silva, Saimon F.; Stroj, Sandra; Rota, Michele; Höfling, Sven; Huber-Loyola, Tobias; Rastelli, Armando; et al. (ACS Photonics)
Beamsplitters represent fundamental components in both classical and quantum optical systems, enabling the distribution of light, as well as the generation of interference, superposition, and entanglement. However, optical networks constructed from conventional bulk 2 × 2-beamsplitters encounter inherent scalability issues, as the number of required beamsplitters scales quadratically with the number of optical modes for a fully connected network. Metasurfaces offer a promising route to overcome these constraints. By manipulating light at the wavelength scale, compact optical components with advanced functionalities can be constructed, which address several modes simultaneously. In this work, we design and experimentally utilize a metasurface as a multiport beamsplitter. Furthermore, we realized a multimode interferometer composed of two cascaded metasurfaces. We characterize the individual and cascaded metasurfaces by using classical light, showing controllable splitting ratios through tunable phase relations. We then expand the approach to quantum light, employing single photons to demonstrate second- and third-order photon correlations as well as single photon interference across multiple spatial paths. These results establish metasurface-based multiport beamsplitters as a scalable and reconfigurable platform bridging classical and quantum photonics.
Keywords: metasurface; beamsplitter; interferometer; quantum network; single photons; nanophotonics

Polarization- and Wave-Vector Selective Optical Metasurface with Near-Field Coupling - Wetter, Helene; Wingenbach, Jan; Rehberg, Falk; Gao, Wenlong; Schumacher, Stefan; Zentgraf, Thomas (ACS Photonics)
Metasurfaces are powerful tools for manipulating light using small structures on the nanoscale. In most metasurfaces, near-field couplings are treated as being unfavorable perturbations. Here, we experimentally investigate a structure consisting of sinusoidally modulated silicon waveguides where near-field coupling of local resonances leads to negative coupling, i.e., a negative coupling constant. This gives rise to wave-vector-dependent eigenstates of elliptical, linear, and circular polarizations. In particular, fully circular polarization states are not only present at a single point in momentum space (k-space) but also along a line. This circular polarization line, as well as a linear polarization line, emanates from a polarization degeneracy at the Dirac point. We experimentally validate the existence of these eigenstates and demonstrate the energy-, polarization-, and wave vector dependence of this metasurface as well as its sensitivity to fabrication tolerances. By tuning the incident k-vector, certain polarization-energy eigenstates are strongly reflected, allowing for uses in angle-tunable polarization filters and light sources.
Keywords: metasurface; waveguides; Dirac point; polarization; negative coupling